Evaluation of quick and dirty DNA extraction methods for marker-assisted selection in rice (Oryza sativa L.) - Collard, B. C. Y.; Das, A.; Virk, P.S.; Mackill, D.J. (Wiley, 2007)
Six simple methods for extracting DNA from rice seedlings were evaluated for marker‐assisted selection (MAS). The assessment of each method was based on PCR amplification of SSR markers, DNA yield and purity, time and cost. Based on these criteria, two methods were selected as being superior to other methods. The best two methods included the standard method developed at the International Rice Research Institute (IRRI), which utilizes a sodium dodecyl sulfate extraction buffer followed by chloroform/isoamyl alcohol extraction and a previously published method using sodium hydroxide and Tris. These two methods produced nearly identical PCR amplification results. The sodium hydroxide method is considerably simpler, quicker and cheaper than the standard IRRI method, and may be particularly useful for many applications of MAS or high‐resolution mapping. This method was also adapted into an effective high throughput method utilizing 96‐well plates emphasizing its versatility.